Low Doses of Heparin and Heparin Dihydergot in Postoperative Thromboprophylaxis in Gynaecological Patients - Urlep-Šalinović, Vera; Jelatancev, Biserka; Gorišek, Borut (Thrombosis and Haemostasis, 1994)
A prospective study of postoperative thromboembolic prophylaxis involving 500 gynaecological patients was performed to compare the effectiveness and safety of low doses of heparin (LDH) and heparin-dihydergot (HDHE). In the LDH group 255 patients (51%) aged 26-84 were included, in the HDHE group there were 245 patients (49%) aged 34-86. Both groups were well matched with respect to risk factors, duration of surgery, type of operation, volume of blood transfused and duration of prophylaxis. Thromboembolism was detected in 48 patients (9.6%): 26 patients (10.2%) in the LDH group and 22 patients (9%) in the HDHE group. In the LDH group isotopic deep vein thrombosis (DVT) was found in 23 patients (9%), five of them had pulmonary embolism (PE), detected by lung perfusion scanning without clinical signs of PE, three patients developed clinical PE without detected DVT. In the HDHE group, 22 patients (9%) had isotopic DVT and five of them had PE detected by lung perfusion scanning. In the incidence of TE there was no statistically significant difference between the two groups (p >0.1). Within two months after surgery late clinically manifest TE confirmed by isotopic venography developed in five patients (1.9%) in the LDH group and in one patient (0.4%) in the HDHE group. Wound haematomas appeared in 8 patients (3.1%) in the LDH group and in 9 patients (3.7%) in the HDHE group. There were no ischemic complications (ergotism) in the HDHE group. The HDHE prophylaxis proved no more effective and was ten times more expensive than the usual prevention with LDH.